Inverse simulation to optimize the rib-profile in a rectangular flow-channel. (May 2020) - Min, Chunhua; Chen, Jinyue; Yang, Xuguang; Wang, Kun; Xie, Liyao
Abstract: An inverse optimization is performed for the shape (profile) of a rib-element that is located within a rectangular flow-channel. The optimization is useful to improve not only heat transfer but also to reduce the pressure drop of the channel. A simplified conjugate-gradient method and a multi-objective collaborative optimization method were used to find a profile inversion simulation model, where the shape is constantly updated until the performance evaluation factor reaches a maximum. It is found that inversion-optimization can effectively improve the overall performance of the system when the area of a rib base is given. For different heights and different shapes, the simulation always produces the same optimal solution. Furthermore, when the number of points reaches a certain number, the shape does not change nearly. One specific profile, which is obtained for Re  = 8000, performs always better than the triangular rib surface, even though it does not represent the ideal shape for all cases. Finally, an additional optimization is carried out for different Reynold numbers. For the final optimized geometry, as the Reynold number increases from 3000 to 30, 000, the objective function increases from 1.942% to 11.79%.